2004
DOI: 10.1111/j.1346-8138.2004.tb00639.x
|View full text |Cite
|
Sign up to set email alerts
|

A Cross‐Sectional Analysis of Quality of Life in Japanese Acne Patients Using the Japanese Version of Skindex‐16

Abstract: We measured the quality of life of Japanese patients with acne using the Japanese version of Skindex-16, a semantically equivalent and validated translation of the original version produced by Chren et al. A total of 210 acne patients were enrolled in this study. The results showed that patients with acne experienced more severe emotional effects from their skin disease than functional or symptomatic effects. The scores for emotional aspects were related to the severity of the patients' acne following a prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 8 publications
2
28
0
1
Order By: Relevance
“…Our former study showed that the emotional QOL of acne patients was more affected when compared with other skin disorders like benign growth, eczema and psoriasis 8,10 . The present survey also showed high scores on the emotions scale at the initiation of the study, and both emotions scale score and total score improved significantly in all groups after treatment.…”
Section: Discussionsupporting
confidence: 63%
“…Our former study showed that the emotional QOL of acne patients was more affected when compared with other skin disorders like benign growth, eczema and psoriasis 8,10 . The present survey also showed high scores on the emotions scale at the initiation of the study, and both emotions scale score and total score improved significantly in all groups after treatment.…”
Section: Discussionsupporting
confidence: 63%
“…Concerns among acne patients are scarring, inflammatory and non‐IL; most patients are anxious to resolve the acne without leaving scars, and patients choose treatment for cosmetic reasons. It has also been reported that patients with acne suffer from low quality of life concerning emotional condition . Therefore, it is important to start appropriate treatment at an early stage to avoid the formation of IL and non‐IL and to prevent transition to nodules/cysts and scarring .…”
Section: Discussionmentioning
confidence: 99%
“…Acne is known to have a major influence on patient QOL, and it has been reported that QOL deteriorates as the severity of symptoms increases. 2,14 However, to date, there have been no reports on the impact of acne scars per se on QOL. This study is the first to demonstrate that acne scars impair QOL, based on assessment using the DLQI (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has a high lifetime prevalence, and is known to negatively affect quality of life (QOL). 1,2 The World Health…”
Section: Introductionmentioning
confidence: 99%